Reduction in Estimated Glomerular Filtration Rate in Patients with Elevated Blood Urea Nitrogen but Normal for any Other Markers of Kidney Damage - Xu Xiaoyong; Su Jianrong; Diao Zongli; wei Wei (Journal of Nephrology Advances, 2016)
Background: It is unclear whether patients who present with elevated blood urea nitrogen (BUN), but are normal for other markers of kidney damage, are prone to develop chronic kidney disease (CKD). This study therefore investigated estimated glomerular filtration rate (eGFR), a marker of CKD, in these patients. Methods: Patients with elevated BUN but normal for other markers of kidney damage who were followed-up for ≥48 months in our outpatient clinics were retrospectively evaluated. BUN, eGFR, and serum creatinine concentrations in the patient group were compared with findings in an age- and sex-matched control group. Results: At baseline, BUN concentration was significantly higher in the patient than that in the control group (8.30±1.10 vs 5.05±0.91 mmol/L; p <0.01), but eGFR (111.94±18.62 vs 111.25±14.63 ml/min/1.73m2) and serum creatinine concentrations (87.23±8.59 vs 72.39±10.06 µmol/L) were similar. At 1 year, however, eGFR in the patient group was significantly lower than in the control group (95.39±18.52 vs 108.17±16.99 ml/min/1.73m2; p < 0.01), and was significantly lower than in the patient group at baseline (95.39±18.52 vs 111.94±18.62 ml/min/ 1.73 m2, p < 0.01), with these differences becoming more pronounced over time. Conclusions: Patients with elevated BUN but normal for other markers of kidney damage show significantly lower eGFR over time than matched controls.
Keywords: Blood Nitroten